Synthesis of (9Z, 12E)-, (9E, 12Z)-[1-14C]-linoleic acid, (9Z, 12Z, 15E)-, (9E, 12Z, 15Z)-[1-14C]-linolenic acid and (5Z, 8Z, 11Z, 14E)-[1-14C]-arachidonic acid - Thierry Enard; Jean Michel Vatéle; Olivier Berdeaux; Didier Poillain; Jean Pierre Nöel (Grasas y Aceites)
Trans polyunsaturated fatty acids are produced in vegetable oils during heat treatment (240-250 °C).ln order to study the metabolic pathway of 9c, 12t and 9t, 12c linoleic acid and 9c, 12c, 15t and 9t, 12c, 15c linolenic acid, these products were prepared labelled with carbon 14 in the carboxylic position. 5c, 8c, 11c, 14t-Arachidonic acid was also labelled on the carboxylic position with carbon 14 in order to study its physiological effects. To introduce the labelling (E)-bromo precursors with a 17 carbons chain or a 19 carbon chain were needed. The different syntheses were done by elongation steps and creation of cis double bonds via highly stereospecific Wittig reactions. The radioactive carbon atom was introduced from [14C]-potassium cyanide. The final radioactive fatty acids had a specific activity greater than 50 mCi/mmol and a radioactive purity better than 99 % for linoleic and linolenic and better than 98.6 % for arachidonic acid.